Anomalous Reduction of the Total Suspended Matter During the COVID-19 Lockdown in the Hooghly Estuarine System - Jayaram, Chiranjivi; Roy, Rajdeep; Chacko, Neethu; Swain, Debadatta; Punnana, Ramunaidu; Bandyopadhyay, S.; Choudhury, S. B.; Dutta, Dibyendu (Frontiers in Marine Science, 2021)
The impact of the coronavirus disease 2019 (COVID-19) lockdown in the Hooghly estuarine region, India is assessed using the total suspended matter (TSM) concentration. The estimation of TSM is performed using Landsat-8/operational land imager (OLI), and an intercomparison of TSM load during the pre-lockdown and lockdown periods is done. It is observed that during the lockdown period, TSM reduced by 30–50%. This is a significant observation considering the ecological balance of the region and the fact that it is home to the largest mangroves in the world. This change in suspended matter presumably reflects the influence of reduction in anthropogenic activities owing to the COVID-19 lockdowns, such as industries, closure of shipping activities (through less dredging), and brick kilns (through less sediment removal), which are generally the primary contributors in this region. Even though these observed changes are representative of the positive influence of the COVID-19 lockdown, its implications in estuarine biogeochemistry still remain poorly quantified. The decrease in TSM content may increase light penetration, thereby increasing the primary productivity. In addition, low sediment load reaching the Bay of Bengal could influence the carbon export due to reduction in ballasting effect as reported from this region. In summary, the influence of the COVID-19 lockdown on the biogeochemistry of the aquatic ecosystem appears rather complex than thought earlier and may vary regionally based on local hydrodynamics. The analysis elucidates the complex interplay of regional lockdown and its implication in modulation of local biogeochemistry. However, the relative importance of each process in the Hooghly estuary remains to be fully evaluated.